Terrorism and disaster new threats, new ideas - Clarke, Lee Ben (Research in social problems and public policy, 2003)
The terror attacks of 9.11 signalled that people are increasingly put at risk of not only terrorism but natural and technological disasters as well. Since 9.11 scholars have been asking new questions about catastrophe and made important and interesting innovations in methods, concepts, and theories regarding disaster and terror. This volume brings together a creative set of papers, most of which are about the 9.11 attacks. They draw from several disciplines to address key questions: what lessons does the response to the collapse of the World Trade Center have for disaster planning? what has 9.11 meant for civil liberties in the US? how will survivors react over the long run? and how do we conceptualize panic and mass response?